A Voice of the US Southwestern Border: The 2012 "We the Border: Envisioning a Narrative for Our Future" Conference. (June 2013) - Heyman, Josiah McC
In July 2012, a diverse group of US residents living near the US-Mexico border met in El Paso, Texas for a conference entitled, We the Border: Envisioning a Narrative for Our Future. This paper describes their vision for the US-Mexico border that is at odds with the widespread view of the border as a threat to the United States. These border residents viewed their region as a set of human communities with rights, capacities, and valuable insights and knowledge. They embraced an alternative vision of border enforcement that would focus on "quality" (dangerous entrants and contraband) over "quantity" (mass migration enforcement). They called for investments in the functionality and security of ports of entry, rather than in between ports of entry. They noted the low crime rate in US border cities, and examined how policies of not mixing local law enforcement with federal immigration enforcement contributed to this achievement. They saw the border region as the key transportation and brokerage zone of the emerging, integrated North American economy. In their view, the bilingual, bicultural, and binational skills that characterize border residents form part of a wider border culture that embraces diversity and engenders creativity. Under this vision the border region is not an empty enforcement zone, but is part of the national community and its residents should enjoy the same constitutional and human rights as other US residents. The conference participants emphasized the necessity and value of accountability and oversight of central government enforcement operations, and the need for border communities to participate in federal decision-making that affects their lives.